Religion as a protective factor against adolescent smoking habits: evidence from Spain - Jorge de Andres-Sanchez; Angel Belzunegui-Eraso; Sonia Fernández-Aliseda (Health for All Nations, 2021)
Background: There are a wide number of assessments suggesting that being a member of a religious community inhibits adolescents' risky behaviours and, consequently, can act as a protective factor against the consumption of smoking substances. Methods: We have analysed a structured questionnaire answered by 1935 adolescents from Tarragona (Spain). Results: We have found that variables linked to family were the principal explanatory factors of adolescents' smoking habits. Living with two parents was a protective factor against tobacco and cannabis use since its Incidence Rate Ratio (IRR) was clearly below 1 (p<0.01). So, whereas living with one parent showed an IRR>1 (p<0.05), adolescents that live without parents presented an IRR close 2 (p<0.05 for tobacco and p<0.01 for cannabis). However, having a religious confession also influence smoking substance use in adolescents (IRR close to 0.85 with p<0.01). Conclusion: We found a clear preventive effect in belonging to a religious community. Moreover, this protective effect was less intense, but not statistically significant, for Catholics than for members of other confessions.